2021
DOI: 10.1002/ajh.26368
|View full text |Cite
|
Sign up to set email alerts
|

Tracking immature reticulocyte proteins for improved detection of recombinant human erythropoietin (rhEPO) abuse

Abstract: Athletes abuse recombinant human erythropoietin (rhEPO) and erythropoiesis stimulating agents to increase hemoglobin mass and improve performance. To evade detection, athletes have developed sophisticated blood doping regimens, which often include rhEPO micro-dosing. Detection of these methods requires biomarkers with increased sensitivity and a sample matrix that is more amenable to frequent testing in the field. We have developed a method to measure two immature reticulocyte proteins, CD71 and ferrochelatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Additionally, IRF can be used as a marker for rEPO 7 and Cox et al showed that immature reticulocyte proteins measured in dried blood spots (DBS) showed a larger response to rEPO than RET%. 8 Since androgens can also be quantified in DBS, 30 co-monitoring of blood parameters and steroids in DBS may be possible in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, IRF can be used as a marker for rEPO 7 and Cox et al showed that immature reticulocyte proteins measured in dried blood spots (DBS) showed a larger response to rEPO than RET%. 8 Since androgens can also be quantified in DBS, 30 co-monitoring of blood parameters and steroids in DBS may be possible in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Since, in the future, more samples with both blood parameters and serum hormones may be available, it is of continuous interest to understand the interactions between the different ABP modules. Additionally, IRF can be used as a marker for rEPO 7 and Cox et al showed that immature reticulocyte proteins measured in dried blood spots (DBS) showed a larger response to rEPO than RET% 8 . Since androgens can also be quantified in DBS, 30 co‐monitoring of blood parameters and steroids in DBS may be possible in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A valuable alternative to the expensive and labor-intensive (9) direct detection of rHuEPO is the indirect approach of the Athlete Biological Passport (ABP). The ABP hematological module longitudinally monitors hemoglobin concentration ([Hb]), reticulocyte percentage (RET%), a combined score based on [Hb] and RET% also known as the OFF-hr score defined as [Hb]-60 Â √[RET%] (10), and the multiparametric Abnormal Blood Profile Score (ABPS) (11).…”
mentioning
confidence: 99%